ESTABLISHMENT TECHNIQUES: EFFECT ON GROWTH POTENTIALS OF SYNSEPALUM DULCIFICUM SEEDLINGS - Yisau, J. A. (FUDMA Journal of Sciences, 2023)
One of the most common errors in tree planting is to adopt the wrong method which can cause serious problems after planting out. The study elucidated the effect of some plantation establishment techniques on growth potentials of Synsepalum dulcificum seedlings. This research was carried out at the forest nursery of the Federal University of Agriculture Abeokuta, Ogun State, Nigeria. Techniques tested were planting depth (9cm, 18cm and 27cm), planting width (200cm and 400cm) and fertilizer application (with and without organic fertilizer). Obtained data was analyzed using Analysis of Variance and Fisher’s Least Significant Difference was used to separate significant means. Results showed that number of leaves (53.13), height (24.50 cm), collar diameter (4.88 mm) and root length (42.41 cm), Fresh weight (18.46 g), turgid weight (19.10 g), shoot dry weight (2.62 g), root dry weight (4.99 g) were significantly (p<0.05) in seedlings established 27cm deep. Total dry weights (4.03 g and 7.79 g) were significantly (p<0.05) increased in seedlings spaced of 2m apart and the interaction of 2m spacing and 27cm depth respectively while 4m planting space enhanced seedling chlorophyll content (68.96 mg/l) significantly (p<0.05). Hence, Sysepalum dulcificum seedlings are best established 27cm deep and 2m by 2m spacing for maximum growth.